2013
DOI: 10.4172/2161-0703.1000120
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation of Pott?s disease of the Spine in Adult Sudanese Patients

Abstract: ResultsIn this study, hundred patients with Pott's disease of the spine were recruited. 60 patients (60%) were females and 40 patients (40%) were males. The majority of the patients fall in the age group 45-54 years, which constituted 25 cases (25%) of the study group, followed by the age group 15-24 years, 22 cases (22%). The groups 65-74, 35-44 and 25-34 constitute 20 cases (20%), 18 cases (18%) and 15 cases (15%) respectively (Table 1). The mean age of presentation in our study was 41 years. In 36 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Tuberculosis of spine usually presents with 3 common signs/symptoms: systemic toxemia, osseous lesion and neurological involvement. 4 In our patient, we observed systemic toxemias, for example, fever, anorexia, weight loss and osseous lesion like chest pain. Gibbus was present.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Tuberculosis of spine usually presents with 3 common signs/symptoms: systemic toxemia, osseous lesion and neurological involvement. 4 In our patient, we observed systemic toxemias, for example, fever, anorexia, weight loss and osseous lesion like chest pain. Gibbus was present.…”
Section: Discussionmentioning
confidence: 98%
“…Tuberculosis of the spine affects mainly mid and lower thoracic (67.0%) T5 to T8, upper thoracic (17.2%) T1 to T4, lumber (10.4%) and cervical (3.5%) spine. 4 Infection gradually involves the anterior aspect of the intervertebral joints, spread behind the anterior longitudinal ligament to involve the adjacent vertebra and intervertebral disc. Eventually overlying disc dies as a result narrowing and subsequent vertebral collapse.…”
Section: Introductionmentioning
confidence: 99%
“…Laryngeal cancer is one of the most predominant cancers of the upper respiratory tract 18 . It is rare in individuals under 60 years of age with three quarters of all diagnoses occurring in people over 60 19 . In the current study, the mean age of the Worldwide, laryngeal cancer occurs more commonly in men than in women 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…This delay may be because of the chronicity of the disease, socio-economic factors, ignorance and missed early diagnosis. Ahmed et al [4] reported average four months lapse between onset of symptoms and diagnosis but sometimes it can be longer than this [5] . Constitutional symptoms were present in about 76% patients.…”
Section: Discussionmentioning
confidence: 99%